Detrital zircon ages from Neoproterozoic and Early Paleozoic conglomerate and sandstone units of New Brunswick and coastal Maine:: implications for the tectonic evolution of Ganderia - Fyffe, Leslie; Barr, Sandra; Johnson, Susan; McLeod, Malcolm; McNicoll, Vicky; Valverde-Vaquero, Pablo; van Staal, Cees; White, Chris (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 2009)
ABSTRACT Detrital zircon ages were determined for conglomerate and sandstone samples from six fault-bounded belts in New Brunswick and coastal Maine. Formations sampled included the Martinon (Brookville belt), Flagg Cove (Grand Manan Island belt), Matthews Lake (New River belt), Ellsworth (Ellsworth belt), Calais (St. Croix belt), and Baskahegan Lake (Miramichi belt). Their maximum age of deposition is based on the youngest detrital zircon population and minimum age of deposition based on stratigraphic, paleontological, and cross-cutting intrusive relationships. The determined range of depositional ages are: Martinon between 602 ± 8 (youngest zircons) and 546 ± 2 Ma (age of cross-cutting intrusion); Flagg Cove between 574 ± 7 (youngest zircons) and 535 ± 3 Ma (age of cross-cutting intrusion); Matthews Lake between 539 ± 5 (youngest zircons) and 514 ± 2 Ma (age of overlying volcanic rocks); Ellsworth between 507 ± 6 (youngest zircons) and 504 ± 3 Ma (age of overlying volcanic rocks); Calais between 510 ± 8 (youngest zircons) and 479 ± 2 Ma (graptolite zone); and Baskahegan Lake between 525 ± 6 (youngest zircons) and 488 ± 2 Ma (graptolite zone). All samples are dominated by Neoproterozoic (Gondwanan) zircon populations. The Early Paleozoic Matthews Lake, Ellsworth, and Calais formations contain main population peaks at 539 ± 5 Ma, 545 ± 4 Ma, and 556 ± 7 Ma, respectively, consistent with derivation mainly from magmatic rocks of the Brookville, Grand Manan Island, and/or New River belts, previously dated at ~553 to ~528 Ma. In contrast, the main peak in the Early Paleozoic Baskahegan Lake Formation is older at 585 ± 5 Ma. The main peak in the Neoproterozoic to Early Cambrian Flagg Cove Formation is at 611 ± 7 Ma with a secondary peak at 574 ± 7 Ma; the former was likely derived from locally exposed igneous units dated at ~618 to ~611 Ma. The Neoproterozoic Martinon Formation exhibits dominant peaks at 674 ± 8 Ma and 635 ± 4 Ma. Ganderian basement gneiss dated at ~675 Ma and intruded by plutonic rocks dated at ~584 Ma in the Hermitage Flexure of Newfoundland are possible sources for these older zircon components in the Martinon and Baskahegan Lake formations. Plutonic rocks in the New River belt dated at ~629 to ~622 Ma may be the source of the younger component in the Martinon Formation. The samples also contain a small number of Mesoproterozoic, Paleoproterozoic, and Archean zircon grains, the latter as old as 3.23 Ga. The presence of zircons in the range 1.07 to 1.61 Ga is consistent with an origin along the peri-Gondwanan margin of Amazonia rather than West Africa. The general similarity of zircon provenance for samples from New Brunswick and coastal Maine suggests that all the Ganderian belts were part of a single microcontinent rifted from the Amazonian craton. The Grand Manan Island and New River belts both record two distinct periods of Neoproterozoic arc magmatism (~629 to ~611 Ma and at ~553 to ~535 Ma) whereas the Brookville belt experienced only a single period of arc magmatism lasting from ~553 to ~528 Ma. These differences are attributed to migration of the younger period of arc magmatism further inboard into Ganderia due to shallowing of the subduction zone. A Penobscot rifted arc system is recorded in the New River and Ellsworth belts from ~514 to ~502 Ma, following migration of Ganderia into the widening Iapetus Ocean. The progressively younger depositional ages of the quartzose sandstone sequences of the Brookvlle belt (Martinon Formation), Grand Manan Island belt (Flagg Cove Formation) and New River belt (Matthews Lake Formation) can be attributed to these episodic periods of quiescence and arc activity along the convergent margin of Ganderia. Subsequent rifting of the Early Ordovician Meductic-Popelogan arc along a segment of the Ganderian margin led to the development of the Middle Ordovician Tetagouche back-arc volcanic activity in the Miramichi belt of central and northern New Brunswick.